2002
DOI: 10.1103/physrevb.65.245305
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of dopant segregation toSiO2/Si(001)interfaces

Abstract: Dopant atoms can segregate to SiO 2 /Si͑001͒ interfaces and be deactivated there. Using phosphorus as a typical example of a donor and guided by results of ab initio calculations, we present a model of donor segregation. We find that P is trapped at the interface in the form of threefold-coordinated atoms. The atomic detailed configuration and the process of P incorporation depend on P concentration C P in the vicinity of the interface. At low C P , phosphorus atoms prefer to substitute Si atoms with dangling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 41 publications
5
28
0
Order By: Relevance
“…A 10 s 1000 • C RTP step however does cause a major deactivation of the layer and increase in segregated Sb (62%) to nearly a monolayer. This concurs with recent theoretical predictions of maximum segregation for As and P [19]. It is also interesting to note that the dechanneling yield after the Si surface peak is constant for all three RTP steps.…”
Section: Ltp Of Low Energy Sb Implantssupporting
confidence: 87%
“…A 10 s 1000 • C RTP step however does cause a major deactivation of the layer and increase in segregated Sb (62%) to nearly a monolayer. This concurs with recent theoretical predictions of maximum segregation for As and P [19]. It is also interesting to note that the dechanneling yield after the Si surface peak is constant for all three RTP steps.…”
Section: Ltp Of Low Energy Sb Implantssupporting
confidence: 87%
“…3͒ suggest that P does not segregate to the interface plane, where P-O bonds are energetically very costly, in agreement with previous results. 27,28 Instead, segregation is predicted to the subinterface Si plane with a small energy gain ͑0.16 eV͒. We also found that segregation of two isolated P dopants on this plane is always preferable against pair formation.…”
Section: Dopant Segregationmentioning
confidence: 81%
“…30 Pair formation is driven by the tendency of neutral dopant atoms to establish their preferred threefold coordination as in PH 3 and AsH 3 molecules. Pairing was also later suggested 27,28,31 to occur at the Si-SiO 2 interface in order to explain the observed dopant pile up for higher implanted doses. 27 We found that a nearest-neighbor P-P pair just below the interface plane lowers its energy ͑by 0.23 eV with respect to two isolated P dopants͒ by breaking the P-P bond ͑P-P distance of 3.28 Å͒ and achieving a threefold coordination for the two dopant atoms ͓Fig.…”
Section: Dopant Segregationmentioning
confidence: 93%
“…In this work we used the spin-polarized version of DFT realized within the FHI96md package [6] based ont he density functional theory (DFT) [7,8] and the pseudo-potential method [9]. This package was previously used with advantage for many systems, including transition metal compositions [10][11][12][13][14]. In all cases, the generalized gradient approximation [15] to description of the exchange-correlation interactions has been chosen and the optimization of the atomic geometry has been performed.…”
Section: Methods and Modelsmentioning
confidence: 99%